PROGRESS IN MATERIALS FOR MICROELECTRONICS AND FURTHER CHALLENGES - Novkovski, Nenad; Skeparovski, Aleksandar; Paskaleva, Albena; Spassov, Decho (Macedonian Academy of Sciences and Arts, 2017)
Development of materials and technologies for microelectronics is required by the needs of the constantly in-creasing level of integration of microelectronics circuits. Increase of the integration level compels downscaling of all the dimensions of devices, which in its turn requires very thin layers with exceptional quality due to rather high elec-tric fields at working conditions. First, technological improvements are adopted aimed at fabrication of materials with uniform quality, geometrical flatness and extremely low density of intentionally introduced defects. Second, new fab-rication methods are developed providing materials with much better quality. Third, new materials showing better properties than the standard (conventional) ones are obtained and developed further.Decreasing the dimensions of the layers changes the nature of the physical phenomena involved in the func-tioning of devices. Quantum mechanical mechanisms are more and more important in the description of the properties of the materials and devices on the nanoscale. The question arises where is the limit of the possibilities of the materi-als and technologies for nanoscale electronics.